Estimation of the intertidal bioerosion rated from well-dated fossil tidal notches in Greece. - Evelpidou, N.; Pirazzoli, P. (Marine Geology, 2016)
In this paper a re-analysis of previous research concerning an uplifted tidal notch developed near the modern harbor of Poros (eastern Cephalonia Island, Ionian Sea, Greece) is undertaken. According to radiocarbon dating, this notch was active between the 4th–6th century AD and 1953 AD, i.e. for at least 1450 years. Recent measurements have shown that the inward depth of the notch profile at well preserved sites is 93 cm. This permits an estimate of the average rate of intertidal bioerosion to 0.64 mm/a for this time period.